Evaluation of opacity in polyethylene fiber reinforced composites - Hasani Tabatabaie M; Hassani Z; Arami S (Tehran University of Medical Sciences, 2010)
"nBackground and Aims: The main objective of this study was to determine the effect of polyethylene fibers and veneering composites in fiber-reinforced resin systems on the opacity (contrast ratio). "nMaterials and Methods: The specimens were divided into four groups. Two groups were used as the control groups, with no reinforcement. The fibers of polyethylene (Fibre-Braid) with special basement composites were used as the reinforced framework materials. Filtek Z250 and GRADIA (shade A2) were used as veneering materials. The total thickness of samples was 3 mm with 13 mm diameter. Specimens were prepared in disk shaped metal mold. The composite materials were light-cured according to their manufacturers' instructions. The contrast ratio (CR) of each specimen was determined on black and white backgrounds using reflection spectrophotometer. Reflectance was measured at intervals of 10 nm between 400 nm and 750 nm. Data were analyzed by two-way ANOVA and Tukey HSD test. "nResults: When contrast ratio were compared among the different types of materials statistically significant differences were observed in both veneering composites (P<0.05). The Z250 resin composite had the lowest CR. It was shown that CR tended to decrease as the wavelength of incident light increased from 400 nm to 750 nm. On the other hand, the most differences in CR between groups were found in longer wavelengths. "nConclusion: It was found that polyethylene fibers reduced the amount of the translucency in FRC samples. The results of this study indicate that light reflectance characteristics, including the wavelength dependence, play an important role for the CR of a fiber-reinforced composite.